KEHARMONISAN RUMAH TANGGA PARA PASANGAN PERNIKAHAN DINI: (Studi Kasus Di Desa Sodo Kecamatan Pakel Kabupaten Tulungagung) - Kiki Ardasiah; Habibi Al Amin (JOURNAL SAINS STUDENT RESEARCH, 2024)
Harmony in the household is the dream of every married couple. Harmony itself can be seen through harmony in the household, a sense of happiness, the rare occurrence of conflict in the household, and mutual feelings of love and affection. However, the reality that occurs in society is that marriages carried out before the age of majority/underage can have an impact on harmony in marriage, but early married couples themselves have strategies to create a harmonious household. The focus of the issues discussed are 1) What are the challenges and obstacles in realizing household harmony. 2) How harmonious are early marriage couples in Sodo Village, Pakel District, Tulungagung Regency. This research aims to find out the problems faced by early married couples and what methods early married couples use to create a harmonious household. This research uses research methods through field research which is descriptive qualitative in nature and data collection through observation, interviews and documentation. The conclusions of this research are as follows: 1) Challenges that occur in the households of early marriage couples in Sodo Village, sub-district. Pakel, District Tulungagung due to several reasons: emotional maturity, financial responsibility, poor communication, changes in roles and family and community pressure. And the obstacles that occur in the households of early marriage couples in Sodo Village, District. Pakel District Tulungagung due to several reasons: dependence of husband and wife on their parents, husband and wife's family interfering too much in their children's affairs, husband and wife not giving each other freedom, inner and outer living that is not fulfilled and differences in cultural and socio-economic backgrounds. Overcoming challenges and obstacles in the household requires awareness, patience and commitment from both parties to grow together and build a solid foundation for a harmonious relationship. 2) Early marriage couples in the village. Sodo District. Pakel District Tulungagung, always strives to make its household a harmonious household by: religious life in the household, creating an atmosphere of peace and feeling of comfort, having good communication between family members, respecting each other and accepting the shortcomings of husband and wife and working together with each other. have a sense of responsibility.